Photodissociation of D2+ induced by linearly chirped laser pulses - Csehi, András; Halász, Gábor J.; Cederbaum, Lorenz S.; Vibók, Ágnes (The journal of chemical physics, 2015)
Recently, it has been revealed that so-called light-induced conical intersections (LICIs) can be formed both by standing or by running laser waves even in diatomic molecules. Due to the strong nonadiabatic couplings, the existence of such LICIs has significant impact on the dynamical properties of a molecular system. In our former studies, the photodissociation process of the D+2D+2<msubsup>D2+</msubsup> molecule was studied initiating the nuclear dynamics both from individual vibrational levels and from the superposition of all the vibrational states produced by ionizing D2. In the present work, linearly chirped laser pulses were used for initiating the dissociation dynamics of D+2D+2<msubsup>D2+</msubsup>. In contrast to the constant frequency (transform limited) laser fields, the chirped pulses give rise to LICIs with a varying position according to the temporal frequency change. To demonstrate the impact of these LICIs on the dynamical properties of diatomics, the kinetic energy release spectra, the total dissociation probabilities, and the angular distributions of the D+2D+2<msubsup>D2+</msubsup> photofragments were calculated and discussed.
Gesehen am 15.12.2020
Im Titel ist "2" in D2+ tief gestellt und "+" hoch gestellt